COVID-19 Vaccine Acceptance in A Private Islamic Boarding School, West Nusa Tenggara - Siti Rahmatul Aini; Iman Surya Pratama; Raisya Hasina; Candra Eka Puspitasari; Ni Made Amelia Ratnata Dewi; Muhammad Abdurrahman Fardiaz; Nurmayanggi Aulia Safitri; Shifa Hasanah; Yazid Maula Arzaqi; Khairun Nissa (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2023)
The COVID-19 vaccination program began in Indonesia in 2020, but it is still unknown how well it has been received by particular communities in places like the West Nusa Tenggara region's Islamic boarding schools. This research aimed to identify the characteristics and factors that contribute to the COVID-19 vaccine's acceptance at the Nurul Islam Sekarbela Islamic Boarding School. In August 2022, a cross-sectional survey was conducted on a stratified random sample of chosen boarding school students using a validated questionnaire. Data on demographic factors, COVID-19 history, religious acceptance, and opinions were all examined descriptively. A total of 124 students, or 62%, gave their informed permission. Based on the findings, it was determined that the Nurul Islam Sekarbela Islamic Boarding School's level of acceptance of the COVID-19 vaccine is still considered low (35%) and in doubt (65%). Acceptance of vaccines is mostly influenced by efficacy, safety, and family recommendations. Acceptance of vaccines is impeded by the dominant fatalistic religious mindset.